Algebra


  1. If   2x +
    1
    =1, then the value of x2 +
    1
    is
    4x64x2









  1. View Hint View Answer Discuss in Forum

    2x +
    1
    = 1
    4x

    On dividing by 2, we get
    x +
    1
    =
    1
    8x2

    On squaring both sides, we get
    x +
    1
    2 =
    1
    8x4

    ⇒  x2 +
    1
    + 2 × x ×
    1
    =
    1
    64x28x4

    ⇒  x2 +
    1
    +
    1
    =
    1
    64x244

    ⇒  x2 +
    1
    =
    1
    1
    = 0
    64x244

    Correct Option: A

    2x +
    1
    = 1
    4x

    On dividing by 2, we get
    x +
    1
    =
    1
    8x2

    On squaring both sides, we get
    x +
    1
    2 =
    1
    8x4

    ⇒  x2 +
    1
    + 2 × x ×
    1
    =
    1
    64x28x4

    ⇒  x2 +
    1
    +
    1
    =
    1
    64x244

    ⇒  x2 +
    1
    =
    1
    1
    = 0
    64x244


  1. If   a + b + c = 2c, find
    a
    +
    c
    .
    a − cb − c









  1. View Hint View Answer Discuss in Forum

    a + b = 2c
    ⇒  a – c = c – b

    ∴ 
    a
    +
    c
    a − cb − c

    =
    a
    +
    c
    c – bb − c

    =
    a
    c
    c – bc – b

    =
    a − c
    =
    c – b
    = 1
    c – bc – b

    Correct Option: B

    a + b = 2c
    ⇒  a – c = c – b

    ∴ 
    a
    +
    c
    a − cb − c

    =
    a
    +
    c
    c – bb − c

    =
    a
    c
    c – bc – b

    =
    a − c
    =
    c – b
    = 1
    c – bc – b



  1. If   a + b + c = 0 then the value of
    a2 + b2 + c2
    is
    ab + bc + ca









  1. View Hint View Answer Discuss in Forum

    a + b + c = 0
    ∴  (a + b + c)2 = 0
    ⇒  a2 + b2 + c2 + 2ab + 2bc + 2ca = 0
    ⇒  a2 + b2 + c2 = – 2ab – 2bc – 2ca

    ∴ 
    a2 + b2 + c2
    ab + bc + ca

    =
    −2(ab + bc + ca)
    = −2
    ab + bc + ca

    Correct Option: B

    a + b + c = 0
    ∴  (a + b + c)2 = 0
    ⇒  a2 + b2 + c2 + 2ab + 2bc + 2ca = 0
    ⇒  a2 + b2 + c2 = – 2ab – 2bc – 2ca

    ∴ 
    a2 + b2 + c2
    ab + bc + ca

    =
    −2(ab + bc + ca)
    = −2
    ab + bc + ca


  1. The value of (2a + b)2 – (2a – b)2 is :









  1. View Hint View Answer Discuss in Forum

    x2 – y2 = (x + y) (x – y)
    ∴  (2a + b)2 – (2a – b)2 = (2a + b + 2a – b) (2a + b – 2a + b)
    = 4a × 2b = 8ab

    Correct Option: A

    x2 – y2 = (x + y) (x – y)
    ∴  (2a + b)2 – (2a – b)2 = (2a + b + 2a – b) (2a + b – 2a + b)
    = 4a × 2b = 8ab



  1. If   a + b + c = m and
    1
    +
    1
    +
    1
    = 0, then average of a2,b2 and c2 is
    abc









  1. View Hint View Answer Discuss in Forum

    a + b + c = m

    and ,
    1
    +
    1
    +
    1
    = 0
    abc

    ⇒ 
    bc + ac + ab
    = 0
    abc

    ⇒  bc + ac + ab = 0
    ∴  (a + b + c)2 = a2 + b2 + c2 + 2(ab + bc + ca)
    ⇒  m2 = a2 + b2 + c2 + 2 × 0
    ⇒  a2 + b2 + c2 = m2
    ∴  Required average =
    a2 + b2 + c2
    =
    m2
    33

    Correct Option: B

    a + b + c = m

    and ,
    1
    +
    1
    +
    1
    = 0
    abc

    ⇒ 
    bc + ac + ab
    = 0
    abc

    ⇒  bc + ac + ab = 0
    ∴  (a + b + c)2 = a2 + b2 + c2 + 2(ab + bc + ca)
    ⇒  m2 = a2 + b2 + c2 + 2 × 0
    ⇒  a2 + b2 + c2 = m2
    ∴  Required average =
    a2 + b2 + c2
    =
    m2
    33